Developmental and reproductive toxicology a practical approach - Hood, Ronald D. (New York : Informa Healthcare, 2012)
"Developmental and Reproductive Toxicology: A Practical Approach, Third Edition is a guide for developmental and reproductive toxicologists. Completely revised and updated, this new edition new chapters covers genomics/proteomics, endocrine disruptors, testing for male and female reproductive toxicity, data interpretation in developmental and reproductive toxicity testing, nonclinical juvenile toxicity testing, and the FDA perspective on risk assessment. It includes material on postnatal developmental milestones and extensive glossaries of developmental defect terminology. Practical and informative, the book bridges the gap between theory and application. It contains insights gained from hands-on experience and gathers information scattered throughout the literature, along with previously unpublished information, into one reference"--Provided by publisher.
1. Principles and mechanisms -- 2. Testing principles and methodology -- 3. Risk assessment and regulatory guidance.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Developmental toxicology; Reproductive toxicology; Electronic books